Efficacy of concurrent chemoradiotherapy combined with nimotuzumab for low-risk T4 stage nasopharyngeal carcinoma: A pilot study. Issue 38 (September 2018) - Zhang, Shuai; huang, Xiaopeng; Zhou, Liya; Lin, Shaomin
Abstract: Background: The purpose of this study was to analyze the efficacy and safety of concurrent chemoradiotherapy combined with Nimotuzumab for low-risk T4 stage nasopharyngeal carcinoma (NPC). Methods: This study included 49 low-risk T4 stage NPC patients treated with concurrent chemoradiotherapy plus Nimotuzumab. The IMRT doses were planning target volume (PTV) 70–72 Gy for gross disease in the nasopharynx, and 66–70 Gy for positive lymph nodes. The doses for high risk and low risk region PTV were 60–62 Gy and 54–56 Gy in 31-33 fractions. All patients received a chemotherapy program consisting of Cisplatin 100mg/m2, day 1, Q3w and were treated by Nimotuzumab (Nimotuzumab 200mg, iv, Qw). Results: All 49 patients completed at least two cycles of chemotherapy and seven weeks of Nimotuzumab. The total efficiency of therapy was 100.0%. The 3-year overall survival (OS), distant metastasis-free survival (DMFS), local-regional control (LRC) and progression-free survival (PFS) rates were 89.7%, 87.8%, 97.9% and 85.7%, respectively. No regional lymph node recurrence was detected. The most serious acute toxicity was mucositis, with prevalence of Grades 0 to IV being 0.0%, 57.1%, 34.7%, 8.2%, and 0.0%, respectively. Late toxicity manifested as Grades I and II xerostomia in 32 and 10 patients. Conclusion: In patients with low-risk T4 stage NPC, concurrent chemoradiotherapy combined with Nimotuzumab yielded an excellent local control rate, and the toxicities were mild and tolerable. Distant metastasis was the main cause of treatment failure.